Hegemony Analysis of Industrial Agriculture in Indonesia - Anggita Indari (Universitas Multimedia Nusantara, 2025)
Decades of massive and often hegemonic industrial agriculture have taken a toll on the environment. The expansion of food estate projects in Indonesia clearly exemplifies this trend. Drawing on Martin Nonhoff’s hegemony analysis, this paper examines a discourse corpus consisting of online media coverage of food estate, alongside social media content from an indigenous food activist. The analysis reveals that industrial agriculture is sustained through a discursive formation that frames these projects as the ultimate solutions for food security and economic welfare. However, this hegemonic project remains contested by civil society organizations. They articulate the discourse of food sovereignty rooted in biodiversity and indigenous knowledge, creating a clear discursive frontier against the state’s industrial narrative.